Japan’s Hard and Soft Power in ASEAN - Heng, Yee-Kuang (2017)
Several significant firsts have been achieved by the Japan Self-Defence Forces (JSDF) which has become more visibly engaged in ASEAN. On the other hand, Japan’s soft power potential also now encompasses its ability to provide joint solutions to shared challenges such as health and ageing, urbanisation and access to clean water supplies.